Experimental Study of Laser Cladding Methods on Water Erosion Resistance to Low Pressure Blades Materials of Steam Turbine - Di Zhang; Pengfei Zhao; Wei Zhao; Yaoyuan Luo; Yonghui Xie (Advances in Condensed Matter Physics)
An experimental apparatus was built to study the effects of liquid-solid impact on laser cladding processing specimens of 17-4PH stainless steel material in the present investigation. Then the result of specimens without laser surface process was compared. The impact effect on the specimens was observed using the three-dimensional digital microscope. The depth of laser cladding and substrate material caused by liquid droplet impact was studied in detail and measured. The accuracy and reliability of the experimental system and computing methods were also verified. The depth of the impact area of laser cladding specimens was distributed in the range of 0.5–1.5 μm while the 17-4PH group was distributed in the range of 2.5–3.5 μm. In contrast with specimens without laser surface processing, the material processed by laser cladding has significantly higher resistance to water erosion.